D-KEFS ST Failure Identifies Multiple Sclerosis Patients With Worse Objective and Self-Perceived Physical and Cognitive Disability - Riccardi, Alice; Puthenparampil, Marco; Rinaldi, Francesca; Ermani, Mario; Perini, Paola; Gallo, Paolo (Frontiers in Psychology, 2019)
Background and Objectives. The Brief Repeatable Battery of Neuropsychological Test (BRB-NT) does not explore the executive functions. We combined BRB-NT and Delis-Kaplan Executive Function System Sorting Test (D-KEFS ST) to obtain a more comprehensive evaluation of cognitive impairment in Multiple Sclerosis (MS) patients. Methods. 137 Relapsing Remitting MS (RRMS) patients underwent a detailed neuropsychological assessment including BRB-NT, D-KEFS ST and self-administrated questionnaires, namely the Multiple Sclerosis Neuropsychological Questionnaire (MSNQ), the Fatigue Severity Scale (FSS) and the Beck Depression Inventory-Second Edition (BDI-II). Results. Fifty-four patients (39.4%) had normal scores in each item of both batteries (cognitive normal), while 64 patients (46.7%) failed in at least one test of BRB-NT but not of D-KEFS ST (BRB-NT impaired) and 18 (13.1%) failed in at least one test of both batteries (BRB-NT+D-KEFS ST impaired). Only one patient (0.7%) failed in D-KEFS ST, but not in BRB-NT and was excluded from further analysis. BRB-NT+D-KEFS ST impaired patients had a significant higher mean disease duration and median EDSS score (15.5±13.6 years and 3.5 respectively) compared to those with only BRB-NT impaired (7.9±9.2, p<0.01 and 2.5, p<0.05) and with cognitive normal patients (6.7±9.4, p<0.005 and 2.0, p<0.01). SDMT was more frequently impaired in BRB-NT+D-KEFS ST impaired patients (77.8%) compared to only BRB-NT impaired ones (20.0%, p<0.001). The failure in D-KEFS ST was associated with the number of failed BRB-NT items (OR 1.46, IC95% 1.07-1.99, p<0.05) and with pathological SDMT z-value (OR 10.56, IC95% 2.50-44.66, p<0.005). Compared to BRB-NT impaired patients and the cognitive normal ones, BRB-NT+D-KEFS ST impaired patients had significant higher MSNQ (p<0.01) and BDI-II (p<0.05) values. Conclusions. D-KEFS ST did not increase the number of cognitively impaired MS patients identified by BRB-NT, but provided a more comprehensive evaluation of cognitive decline. D-KEFS ST identified a subgroup of patients with increased self-perception of cognitive decline, depression and higher physical disability.